Determination of |Vub| from exclusive baryonic B decays - Y.K. Hsiao; C.Q. Geng (Physics Letters B, 2016)
We use the exclusive baryonic B decays to determine the Cabibbo–Kobayashi–Maskawa (CKM) matrix element Vub. From the relation |Vub|2/|Vcb|2=(Bπ/BD)Rff based on B−→pp¯π− and B¯0→pp¯D0 decays, where |Vcb| and Bπ/BD≡B(B−→pp¯π−)/B(B¯0→pp¯D0) are the data input parameters, while Rff is the one fixed by the B→pp¯ transition matrix elements, we find |Vub|=(3.48−0.63+0.87±0.40±0.07)×10−3 with the errors corresponding to the uncertainties from Rff, Bπ/BD and |Vcb|, respectively. Being independent of the previous results, our determination of |Vub| has the central value close to those from the exclusive B¯→πℓν¯ℓ and Λb→pμ−ν¯μ decays, but overlaps the one from the inclusive B¯→Xuℓν¯ℓ with the current uncertainties. The extraction of |Vub| in the baryonic B decays is clearly very useful for the complete determination of the CKM matrix elements as well as the exploration of new physics.